234k views
1 vote
If s(x) = 2 – x2 and t(x) = 3x, which value is equivalent to ? –439 –141 153 443

User Atul N
by
4.8k points

2 Answers

1 vote

Answer:

A: -439

Explanation:

User Rysama
by
5.3k points
0 votes

Answer:

The correct option is -439

Explanation:

We have given that s(x) = 2 – x2 and t(x) = 3x. We have to find the equivalent value.

s(x) = 2 – x2

t(x) = 3x

(s o t)(x)=s(t(x))

s(t(x)) = 2-(3x)^2 = 2-9x^2

So, now putting the value of s of t(x) as (-7) we will get the value as:

(s o t)(-7) = 2-9(-7)^2 = 2 - 9(49)

(s o t)(-7) = 2-441

(s o t)(-7) = -439

Thus the correct answer is option A...

User Graza
by
6.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.